Gameleira, sertão Norte de Minas Gerais: um olhar feminino sobre o feminino camponês - Cunha, Maria das Graças Campolina (2013)
This thesis discusses the interpretation on peasantry history and the female peasants so I chose and welcomed a traditional rural community in Northern Minas Gerais, The Gameleira community between the municipalities of Glaucilândia and Bocaiúva. My aim was to understand the history of this place through the feminine eye and their reports about life, their work and relationships with their family, neighbors and with the sacred, in which reciprocal relations are evident and achieved. The history of this community support the important role woman has in peasantry reproduction, a role little approached in studies on this universe. As man partner woman broke in the untouched soil and changed land into work, besides building the family surviving conditions through work and care addressed to their maintenance. For a better understanding of the subject studied, this research is divided in three parts, each of which established or held different theoretical approaches, dialogues and interpretations. On the first part I conducted a theoretical discussion on the origin and settling of the Brazilian peasantry and the hierarchical relationships that pervade the peasant way of life. On the second part there are theoretical discussions on the construction and changes of the peasant territory in Northern Minas Gerais and the role played by the country woman, both in the past and contemporary period. The third and final part is fruit of my experience in the field; I used ethnographic research methods, aiming the reading of the country Gameleira s woman. I consider that this population remains leading a traditional way of life, at the same time that experience changes due to the current dynamics around them which resignified in the spheres which involve the world work. This re-significance creates a female redeem movement of its endangered visibility and hierarchally constructed, through salaried work and arts craft. In the Gameleira s peasant universe, woman, or the peasant female keep the role of main guardians of their peasantiness and resistance of their way of life, through relations and actions which develop and involve the symbolic spheres of its manifestations.